The Influence of Work Life Balance on the Work Satisfaction of Millenial Doctors - Renatha Verary; Sri Suwarsi; Hendrati Dwi Mulyaningsih (Jurnal sosial dan sains, 2022)
Background: A hospital is in constant demand of holistic service. Different professions and different generations of staff, intertwining with different kinds of demands from all sorts of customers, making a hospital a high-pressure workplace, conduct 24 hours of various activities. This leads to disturbance in work life balance, resulting in dissatisfaction from doctors toward the hospital. From 2015 onward, Gen Y (known as millennial) has taken over as the dominant workforce replacing the Baby Boomers. Purpose: To perceive the level of work life balance from the perception of millennials doctors, how it affects the overall satisfaction, and work satisfaction. Method: This research is conducted in a hospital in Bandung, with 84 participants (chosen with purposive sampling technique). Data was collected through questioners, observations, and interviews. The research method used is the causal relation of X and Y. Results: Out of four dimensions in work life balance, life to work enrichment achieves the highest score, as work to life conflicts is the lowest. The work satisfaction rate in millennial doctors in Bandung is categorized as very good, whereas from five dimensions of satisfaction, workplace satisfaction gets the highest score, and employer satisfaction is the lowest. Research results signify the importance of work life balance in working satisfaction for millennial doctors in a hospital in Bandung. Even though the research showed acceptable results, efforts are still needed to maintain the satisfactory rate for millennial doctors. Conclusion: The conclusions from research results are out of four dimensions in work life balance, life to work enrichment achieves the highest score, as work to life conflicts is the lowest.